2021
DOI: 10.1021/acs.analchem.1c00118
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Nanorods of Phenylboronic Acid Functionalized Pyrene for In Situ Two-Photon Imaging of Cell Surface Sialic Acids and Photodynamic Therapy

Abstract: Sialic acid (SA) plays important roles in various biological and pathological processes. Methods for monitoring and detection of SA are of great significance in terms of fundamental research, cancer diagnostics, and therapeutics, which are still limited until now. Here, a phenylboronic acid (PBA)-functionalized pyrene derivative, 4-(4-(pyren-1-yl)butyramido)phenylboronic acid (Py-PBA), was synthesized and used as a building block for selfassembling into hydrophilic nanorods. The Py-PBA nanorods (Py-PBA NRs) fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…In aqueous basic media, sp 2 -hybridized trigonal planar PBA groups can be converted into sp 3 -hybridized tetrahedral phenylborates, , with which the reaction of the cis -1,2 and 1,3-diol sites of saccharides generates the covalent five- or six-membered rings, respectively. , That is, the covalent coupling between the PBA groups and the cis -diol sites can be greatly facilitated by a basic medium with a pH above the p K a of the PBA group . Accordingly, the boronate affinity-based site-specific labeling of target glycoproteins is pH-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…In aqueous basic media, sp 2 -hybridized trigonal planar PBA groups can be converted into sp 3 -hybridized tetrahedral phenylborates, , with which the reaction of the cis -1,2 and 1,3-diol sites of saccharides generates the covalent five- or six-membered rings, respectively. , That is, the covalent coupling between the PBA groups and the cis -diol sites can be greatly facilitated by a basic medium with a pH above the p K a of the PBA group . Accordingly, the boronate affinity-based site-specific labeling of target glycoproteins is pH-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al demonstrated self-assembly of the amphiphilic 4-(4-(pyren-1-yl)butyramido)phenylboronic acid ( Py-PBA ) in a nanorod (NR) shape in DMSO-water mixture and applied in intracellular two-photon imaging of the sialic acid (SA; plays vital role in many biological and pathological processes) [ 92 ]. The monomer emission of the Py-PBA was at 400 nm.…”
Section: Aie Active Pyrene Conjugates For Bioimagingmentioning
confidence: 99%
“…The above contents demonstrated the imaging ability of PBA-functionalized polymers to glycoprotein-overexpressing cancer cells and developed a controllable imaging system for biological applications. To improve the selectivity of PBA-functionalized small molecules, Li et al designed and synthesized PBA-functionalized pyrene derivatives (Py-PBA) and formed nanorods through self-assembly (Py-PBA NRs) . (Figure B) Py-PBA NRs could bind specifically to SA, which could help Py-PBA NRs locate and image on the cell membrane.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…(C) Mean fluorescence intensity of HepG2 cells in the different samples. Reproduced with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Fluorescence Imagingmentioning
confidence: 99%